2016
DOI: 10.1371/journal.pone.0150859
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Fluconazole and Calcium Channel Blockers against Resistant Candida albicans

Abstract: Candidiasis has increased significantly recently that threatens patients with low immunity. However, the number of antifungal drugs on the market is limited in comparison to the number of available antibacterial drugs. This fact, coupled with the increased frequency of fungal resistance, makes it necessary to develop new therapeutic strategies. Combination drug therapy is one of the most widely used and effective strategy to alleviate this problem. In this paper, we were aimed to evaluate the combined antifung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 41 publications
3
71
0
Order By: Relevance
“…C. glabrata is naturally resistant to azoles due to the presence of less affinity to lanosterol 14 a-demethylase (Erg11p), inherent mechanism for the upregulation of ERG11 (for ergosterol biosynthesis) and ABC transporters (for increased drug efflux). 47 Our results are in agreement with the findings of Liu et al, 40 where it has been shown that AB alone is not much effective against the planktonic cells of C. albicans. 40 Another study has shown that CCH1 mutant of C. glabrata is more susceptible to the azole drugs.…”
Section: Antifungal Susceptibility Testsupporting
confidence: 92%
See 2 more Smart Citations
“…C. glabrata is naturally resistant to azoles due to the presence of less affinity to lanosterol 14 a-demethylase (Erg11p), inherent mechanism for the upregulation of ERG11 (for ergosterol biosynthesis) and ABC transporters (for increased drug efflux). 47 Our results are in agreement with the findings of Liu et al, 40 where it has been shown that AB alone is not much effective against the planktonic cells of C. albicans. 40 Another study has shown that CCH1 mutant of C. glabrata is more susceptible to the azole drugs.…”
Section: Antifungal Susceptibility Testsupporting
confidence: 92%
“…47 Our results are in agreement with the findings of Liu et al, 40 where it has been shown that AB alone is not much effective against the planktonic cells of C. albicans. 40 Another study has shown that CCH1 mutant of C. glabrata is more susceptible to the azole drugs. 35 AB is a known inhibitor of Ca 2+ channel and has shown good affinity with C. glabrata Cch1p, Fig.…”
Section: Antifungal Susceptibility Testsupporting
confidence: 92%
See 1 more Smart Citation
“…Nonetheless, it is clear from our experiments that chemical inhibition of calcineurin is sufficient to abrogate the growth of the vps21⌬/⌬ mutant in the presence of fluconazole. Interestingly, Liu et al (42) showed that dihydropyridine treatment suppresses the fluconazole-induced expression of the two calcineurin subunits, sensitizing azole-resistant C. albicans isolates to fluconazole. Thus, the resensitization of the vps21⌬/⌬ mutant by nisoldipine is also consistent with the mutant's azole tolerance depending upon enhanced calcineurin-dependent responses.…”
Section: Figmentioning
confidence: 99%
“…10,12 For example, combinations of calcium and calcineurin inhibitors with known antifungal compounds have been shown to inhibit the growth of drug resistant fungal strains. [13][14][15][16][17][18][19] Therefore, inhibition of calcineurin signaling is a novel antifungal strategy that both attenuates fungal virulence and increases the efficacy of the existing antifungals with concomitant suppression of antifungal resistance. 10,20,21 Calcineurin is a conserved Ca 2C -calmodulin (CaM) activated protein phosphatase 2B belonging to the phospho-protein phosphatase family of enzymes and is involved in calcium-dependent signaling and regulation of several important cellular processes in both yeasts and filamentous fungi (Fig.…”
Section: Introductionmentioning
confidence: 99%